563 Different right ventricle maladaptation in patients with HFrEF and HFpEF: diagnostic and prognostic implications. (8th December 2021) - Ruocco, Gaetano; Pirrotta, Filippo; Stefanini, Andrea; Barilli, Maria; Cavati, Guido; Palazzuoli, Alberto
Abstract: Aims: The prognostic impact of right ventricular (RV) dysfunction and of pulmonary hypertension (PH) in patients affected by heart failure (HF) is well known. More recently it has been demonstrated that the coupling between the afterload and the function of the right ventricle in terms of TAPSE/PAPS ratio, may provide additional prognostic information. In contrast, sparse and conflicting data have been published regarding the relevance of different echocardiographic features in patients with reduced or preserved ejection fraction. Additionally, RV function and ventricular-arterial coupling is poorly studied in acute setting. We planned a prospective monocentric study aimed at elucidating the role of PH and of RV structure and function, assessed by means of an echocardiographic examination in the early phase of hospital admission of patients with ADHF. We also compared different echo parameters in order to assess the prognostic role in patient affected by HF and reduced ejection fraction (HFrEF) vs. those with preserved ejection fraction (HFpEF). Methods and results: we included 381 patients included in the study, 209 had HFrEF and 172 had HFpEF. All the examinations were performed by cardiologists according to the instructions provided by the American Society of Echocardiography. In all patients LV volumes and diastolic function analysis were performed. A detailed examination of RV dimension and function were achieved by the measurement of right ventricular diameter at basal level, Pulmonary systolic pressure (PAPS), Tricuspid anular peak systolic excursion (TAPSE) and s wave by TDI analysis at RV free wall basal level. Finally longitudinal function was measured at lateral RV wall by post processing strain analysis. Overall, the median TAPSE was 19 (16–21) mm, the median of RVEDD was 40 (36–45) mm, the median PASP was 45 (35–50) mmHg and the median s' wave was 11 (7–14). Patients with HFrEF demonstrated a larger RVEDD compared to HFpEF (44 ± 6 vs. 38 ± 5 P  < 0.05) and more reduced TAPSE (16 ± 4 vs. 20 ± 3 P  < 0.05). Whereas PAPS values were similar in both groups (47 ± 10 vs. 45 ± 10 NS). Conversely, s' wave was much more reduced in HFpEF (9 ± 3 vs. 12 ± 4 P  < 0.05) RV longitudinal strain was reduced in both group but HFpEF population demonstrated more impaired values (−18 ± 5 vs. −22 ± 8; P  < 0.01). TAPSE/PAPS was significantly reduced in HFrEF (0.38 ± 8 vs. 0.43 ± 5 P  < 0.01). Conversely s'/PAPS was more pronounced in HFpEF group (0.25 ± 4 vs. 0.29 ± 7 P  < 0.05). At univariate analysis several parameters were related to outcome: TAPSE ≤ 14 mm, [HR: 1.70 (1.14–2.52); P  = 0.009], PASP≥ 40 mmHg [HR: 1.51 (1.05–2.17); P  = 0.02], RVEDD > 38 mm [HR: 1.88 (1.36–2.61); P  < 0.001], s wave < 9 [HR: 1.88 (1.3–2.4), P  < 0.001], inferior vena cava diameter > 21 mm [HR: 1.90 (1.31–2.75); P  = 0.001]. Therefore TAPSE/PAPS was associated with adverse event in HFrEF but not in HFpEF (HR: 1.75 and HR: 1.02). Whereas, s/PAPS was associated with more increased risk in HFpEF (HR: 1.8 and HR: 1.3). Conclusions: Right ventricular dysfunction and maladaptation are associated with poor outcome in either HFrEF and HFpEF. However tissue excursion and longitudinal strain are much more impaired in HFpEF, whereas RV dilatation and reduced longitudinal function are closely related to HFrEF. Different prognostic values and evaluation may be comprised during the evaluation of HFrEF and HFpEF.